Finger and palm dynamic pressure monitoring for basketball shooting - Hung, C.-F.; Chen, C.-C.; Lin, S.-H.; Chung, T. K. (Journal of Sensors, 2017)
This study verified general inferences on the finger and palm pressure distribution of a basketball player in the moment before that player shoots a basketball through a scientific qualitative testing method. We mounted the sensor on the hands of college basketball players and monitored the dynamic pressure of each player`s hand while the player threw a basketball. The dynamic pressure distribution of the fingers and palm of a basketball player throwing a ball can be verified. According to the experimental results, college basketball players typically use the index finger to control the direction and power of force in the moment before shooting a basketball. This study successfully used a scientific qualitative test method to monitor the dynamic pressure of the fingers and palms of basketball players and verified the general inference that a typical basketball player mainly uses the index finger to control the direction and power of force in the moment before throwing a ball. In the future, this study, measuring the dynamic pressure distribution of the fingers and palm, can be applied to simulate hand manipulation in many biomedical and robotic applications.